Catalytic Enantioselective Synthesis of α‐(Benzylamino)cyclobutanones. Issue 20 (2nd June 2015) - Melis, Nicola; Ghisu, Lorenza; Guillot, Régis; Caboni, Pierluigi; Secci, Francesco; Aitken, David J.; Frongia, Angelo
Abstract: An organocatalytic enantioselective synthesis of α‐(benzylamino)cyclobutanones has been achieved by employing a tandem condensation/intramolecular rearrangement/proton transfer reaction and starting from racemic α‐hydroxycyclobutanone and a selection of benzylamines. This reaction sequence afforded the products in good to high yields with moderate to high enantioselectivities. Abstract : An organocatalytic enantioselective synthesis of α‐(benzylamino)cyclobutanones has been achieved by employing a tandem condensation/intramolecular rearrangement/proton transfer reaction. The reaction sequence began from readily available racemic α‐hydroxycyclobutanone and a variety of benzylamines to afford the products in good to high yields and with moderate to high stereoselectivities.